Evaluasi Pengemasan Produk Susu Pasteurisasi di UMKM X di Kota XX - Luthfi Khairunnisa, Hanindya; Mar’ie Sirajuddin, Muhammad (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2023)
Pasteurized milk is a process of killing pathogenic bacteria that may still be present in milk and some other bacteria can still survive. The purpose of cooling milk is to prevent microbes that destroy milk from developing, so that milk does not experience defects in a relatively short time. Decay microbes cannot grow and develop at a temperature of 3-100°C. Defects in the packaging of pasteurized milk products in X SMEs are one of the problems that need to be observed for further analysis regarding the causes of the problems that occur so that process improvements can be made to minimize losses experienced by X SMEs as a result of packaging defects. Writing a practical work report with the title Packaging Evaluation of Pasteurized Milk Products at MSME X aims to analyze the number of packaging defects in pasteurized milk products, analyze the factors that cause packaging defects that occur and provide evaluation solutions or suggestions to minimize the level of defects and improve the quality of the packaging. pasteurized milk products in SMEs X. The methods used for data collection are direct observation, interviews, and literature study. Solving problems in this practical work using Pareto Diagrams and Fishbone Diagrams. The results of the observation of packaging defects of pasteurized milk products using the Pareto Diagram analysis method show that the average results of the analysis of defects in pasteurized milk packaging in UMKM X occur in dented bottles with a value of 52%. Fishbone diagram analysis shows the factors that cause defects in the packaging of pasteurized milk products which are influenced by human factors, materials, methods, and the environment.